Influence of particle loading, Froude and Stokes number on the global thermal performance of a vortex-based solar particle receiver. (January 2022) - Ang, Daniel; Chinnici, Alfonso; Tian, Zhao F.; Saw, Woei L.; Nathan, Graham J.
Abstract: We report a joint experimental and numerical study on the global thermal performance of a novel windowless vortex-based cavity receiver for potential thermal processing of suspended particles. This systematic study assesses the coupled influence of particle loading, Froude and Stokes number through variation of the inlet mass flowrate, particle size and loading on the global performance of the Solar Expanding Vortex Receiver-Reactor (SEVR) under steady-state conditions. The experiments employ polydispersed CARBO CP ceramic particles that are heated with an 18-kWel Metal Halide three-lamp solar simulator. A numerical study was also performed using computational fluid dynamics (CFD) software ANSYS/CFX 2019 R1. It was found that the particle volumetric loading and Froude number have primary controlling influence, while the Stokes number has a secondary influence on the global performance for these conditions. An overall thermal efficiency of 67% was obtained under high particle loading and Froude numbers. Highlights: Global thermal performance of windowless vortex-based solar particle receiver measured. Particle loading and fluid velocity was found to strongly influence the thermal performance. 3D CFD model of the device is developed and validated against the experimental data. Distribution of heat in the two-phases are affected by operating conditions.